Implementasi Sistem Pembelajaran Kitab Kuning di Madrasah Aliyah Muallimin UNIVA Medan - neliwati, neliwati; Anwar, Khairul; Fahmi, Khairul; Hidayat, Azmar (Tarbawiyah Jurnal Ilmiah Pendidikan, 2024)
This research aims to describe the implementation of the yellow book learning system, to describe the supporting and inhibiting factors in the implementation of the yellow book learning system and to describe the solutions taken to overcome the inhibiting factors in the implementation of the yellow book learning system at Madrasah Aliyah Muallimin UNIVA Medan. This research is field research using descriptive qualitative methods. Data collection in this research used interviews, observation and documentation. Analysis techniques use: data reduction, data visualization, and drawing conclusions/verification. Meanwhile, the data validity test takes the form of source triangulation and technical triangulation. The results of the research show that the implementation of the yellow book learning system at Madrasah Aliyah Muallimin UNIVA Medan adopts an Islamic boarding school approach with practical, active and applicable methods, especially in learning the Al-Qur'an using the tilawati method. The types of books taught include Tafsir Jalalain, Jawahirul Bukhari, Ibnu'Aqil, Kawakib Duriyah, Jawahirul Balaghah, and Minhajut Thalibin. The learning method used is the bandongan method. Supporting factors include the use of books or yellow books and the high enthusiasm of students in learning. However, delivering the material is a challenge due to the variety of students' different educational backgrounds. The proposed solution involves improving learning methods by including interesting stories, support from parents, and motivation from teachers to make understanding the yellow book easier for students.